Energy Crisis and Nuclear Fusion Power - K.C., Hari (Himalayan Physics, 2015)
Due to the rapid industrialization and luxurious life style of mankind all of the non renewable sources of energy are going to finish in near future. To address energy crisis problem it is necessary to search or invent long lasting new sources of energy which could run the world for long term. Here, in this article a attempt has been made to discuss a new source of energy called nuclear fusion process. Several methods made to produce energy from nuclear fusion process are tried to discuss here. Fusion power offers the prospect of an almost inexhaustible source of energy for future generations, but it also presents so far insurmountable scientific and engineering challenges. The main hope is centered on tokamak reactors which confine deuterium-tritium plasma magnetically. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014)Page: 131-136